Rural energy planning remains out-of-step with contemporary paradigms of energy access and development. (January 2017) - Herington, M.J.; van de Fliert, E.; Smart, S.; Greig, C.; Lant, P.A.
Abstract: Billions of people around the world remain without access to modern energy services, the majority of whom live in rural locations. To support the deployment of these critical services, energy planners must consider complex interdisciplinary factors in the process of evaluating and deciding upon locally appropriate energy solutions. A key mechanism for navigating such complexity is to engage relevant local stakeholders in the process. In this study, we apply a systematic review to analyse process-oriented energy planning literature published over the last 35 years to explore the extent that past and present practices reflect current paradigms on energy access and development. The results indicate that the typical approach to evaluate appropriate energy solutions is siloed, disciplined in focus and non participatory. This paper highlights the need for a greater dialogue on participatory practice in the energy agenda to bring closer alignment with contemporary development thinking, and introduces an analytical framework as a way to reflect on this.